Performance analysis of heterostructure-based topological nanophotonic sensor - Amit Kumar Goyal; Ajay Kumar; Yehia Massoud (Scientific Reports, 2023)
Abstract In this manuscript, a heterostructure-based topological nanophotonic structure is proposed for improved sensing performance. The topological effect is realized by connecting two dissimilar one-dimensional photonic crystal structures having overlapped photonic bandgaps. The structural parameters are optimized to regulate and alter the dispersion characteristics, which results in the opposite Zak phases. This demonstrates a robust topologsical interface state excitation at a 1737 nm operating wavelength. Further, a topological cavity structure having resonance mode at 1659 nm is formed by replacing the interface layers with a defect layer. The mode excitation is confirmed by analyzing the electric field confinement at the interface. The sensing capability of the structure is analytically evaluated by infiltrating different analytes within the cavity. The analytical results demonstrate the device’s average sensitivity of around 774 nm/Refractive index unit (RIU) along with an average high Q-factor and figure of merit of around 5.2 × 104 and 2.6234 × 104 RIU−1, respectively. Because of the higher interface mode field confinement, the proposed structure exhibits a 92% higher sensitivity, 98% improved Quality factor, 206% improvement in figure of merit, and 86% higher interface field confinement than conventional Fabry–Perot resonator structures. Thus, the proposed topological cavity structure shows its broad sensing ability (Refractive Index: 1.3–1.6) along with a low-cost, simple fabrication and characterization process, promoting the development of highly sensitive planner nanophotonic devices.